MAPPING AUDIOVISUAL TRANSLATION: SUBTITLING, REVOICING, AND ACCESSIBILITY PRACTICES - Fakhriddin Bakiev (PT. Antis International Publisher, 2026)
Objective: This review article examines the development of audiovisual translation (AVT) with a particular focus on subtitling, revoicing, and accessibility-oriented practices. Drawing on international AVT scholarship and recent studies from the Uzbek context, the article maps key theoretical approaches, research trends, and methodological shifts in the field. Method: The review highlights subtitling as a dominant mode of screen translation, the persistence of culturally and economically conditioned revoicing practices, and the increasing importance of accessibility as a core paradigm in AVT research. Results: Special attention is given to linguistic, pragmatic, and linguocultural issues, as well as to corpus-based and pedagogical approaches. The article identifies existing gaps and future research directions, particularly in underrepresented languages and emerging audiovisual cultures. Novelty: The findings contribute to a more inclusive understanding of audiovisual translation as a multimodal and socially embedded form of mediated communication.